German-Sino collaboration in science, technology and innovation - Rainer Frietsch; Ulrike Tagscherer (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2014)
[Introduction ...] This paper describes the current STI policies of the Sino-German collaboration from a German perspective. It starts with the policies and the actions on the governmental level. Section three tries to briefly depict the effective implementation and the outcomes of these policies and individual actions. It uses empirical data to describe the current status and the evolution of the Sino-German exchange in science, technology and in-novation. Scientific publications and especially co-publications provide a sketch of the science collaborations. Patents and co-patents offer an indication of the technology collaboration as well as an assessment of the attractiveness of the (technology) markets. Finally, foreign trade data also offers a view on the industrial exchange. Profiles in all three dimensions convey a broad picture of complementarities and competition between China and Germany. Section four discusses and summarizes the findings.
urn:nbn:de:0011-n-2892725
Keywords: 330